O governo Lula: política, governabilidade e hegemonia - Mecca, Andréia Cordeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This paper discusses the reconciliation of classes within the Lula government. For this, it is understood as important to reflect on the implementation of the neoliberal model in the country and the Brazilian subordinate position in the new world order. Later, makes the analysis of alliances and strategies of the government before the 2002 election. From the signed agreements, develops the study of political and economic measures rolled out in the first Lula term, and the international context and the infighting as background. Make explicit as this government enabled the emergence of large national groups and the implications for the reorganization of the dominant bloc. The working class is also analyzed, seeking to understand which policies and measures were directed to the proletariat, in addition to a brief history of the most important trade union federation in the country, the CUT . The objective is to demonstrate the movements of the proletarian fractions. Finally, the analysis draw a parallel between the two classes under the Lula government, trying to show the conditions that gave the possibility to reconcile these classes, which led to extensive governability of Lula.

O presente trabalho procura discutir conciliação de classes dentro do governo Lula. Para isso, entende-se como importante refletir sobre a implementação do modelo neoliberal no país e a inserção subordinada brasileira na nova ordem mundial. Posteriormente, faz-se uma análise das alianças e estratégias do governo antes da eleição de 2002. A partir dos acordos firmados, desenvolve-se o estudo das medidas políticas e econômicas desenroladas por Lula em seu primeiro mandato, tendo o contexto internacional e as disputas internas como pano de fundo. Explicita-se como esse governo possibilitou o surgimento de grandes grupos nacionais e quais as consequências para a reorganização do bloco dominante. A classe trabalhadora também é analisada, buscando-se compreender quais políticas e medidas foram direcionadas ao proletariado, além de fazer um breve histórico da central sindical mais importante do país, a CUT. O objetivo é demonstrar os movimentos das frações proletárias. Por fim, é apresentado o paralelo entre as duas classes sob o governo Lula, procurando mostrar as condições que deram a possibilidade de conciliação dessas classes, o que gerou a ampla governabilidade de Lula.
Keywords: Brasil Presidente (2003-2006 : Lula); Brasil Presidente (2007-2010 : Lula); Neoliberalismo; Política econômica; Política social